2022
DOI: 10.1155/2022/9330699
|View full text |Cite|
|
Sign up to set email alerts
|

Action Recognition Model in Choral Conducting Teaching in Colleges and Universities under New Media Environment

Abstract: In current college music education, choral conducting is a required course for students. The course implementation aims to cultivate excellent and high-quality choral conductors. The requirements for choral conducting teaching in college music education under the new media environment have been further improved. First, this study gives the value of applying new media technology in choral conducting teaching in colleges and universities. Then, based on the key point that choral conductors’ expression of music m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…As a type of cultural and leisure activity, amateur choral activity promotes holistic perception and assimilation of knowledge about the multifaceted palette of the art. It is an effective means of forming the creative potential of its participants, developing skills, inclinations, and talents, and socializing them with their further objectification in the individual sphere of life creativity (Jiao, 2022). Choral activity as a type of cultural and leisure activity performs an educational function.…”
Section:  Active Participation In Various Types Of Social Activities;mentioning
confidence: 99%
“…As a type of cultural and leisure activity, amateur choral activity promotes holistic perception and assimilation of knowledge about the multifaceted palette of the art. It is an effective means of forming the creative potential of its participants, developing skills, inclinations, and talents, and socializing them with their further objectification in the individual sphere of life creativity (Jiao, 2022). Choral activity as a type of cultural and leisure activity performs an educational function.…”
Section:  Active Participation In Various Types Of Social Activities;mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%